Teachers, Parents, and the Digital Challenge: Understanding Islamic Character Formation in Singapore’s Madrasa Education - Ulil Amri Syafri; Hanafiah Bin Budin (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study explores the practical implementation of Islamic character values within classroom and school environments in Singaporean madrasas. It also investigates how parents and teachers perceive the effectiveness of character education. Employing a mixed-methods approach within a sequential exploratory design, this research integrates qualitative data from interviews, observations, and documentation with quantitative data from questionnaires.  To provide a comprehensive understanding. Case studies were conducted at Madrasa Wak Tanjong Al-Islamiah (a full-time madrasa) and Andalus Corporation (a part-time madrasa). Qualitative findings were used to identify relational patterns among variables, which were then tested using quantitative surveys. The findings reveal that Islamic character education is implemented through teacher exemplars, social interactions, and structured religious activities that form part of the madrasa’s institutional culture. Both teachers and parents perceive the process positively, acknowledging its systematic and value-based nature. This layered process emphasizes character formation not merely as knowledge transmission, but as the internalization of values through habituation and spiritual development. A key challenge, however, lies outside the madrasa-particularly digital distractions such as social media and unfiltered online content, which often contradict the values taught within the madrasa context.